STEAM Study on Local Wisdom of Batik Tulis Yogyakarta to Develop Science Teaching Materials - Dwi Agnes Setianingrum; Jumadi Jumadi (Postgraduate, University of Mataram, 2023)
Batik tulis is one of Indonesia's cultural heritage which is rich in meaning and philosophical value. Batik tulis crafts are scattered in various parts of the region with their respective characteristics. One of the regions producing batik art is Yogyakarta. The process of making batik is often taught in arts and culture subjects in the context of preserving Indonesian culture, even though the process of making batik can also be integrated into science learning. There are many components in the process of making batik tulis related to natural science material. This research aims to determine aspects of STEAM (Science, Technology, Engineering, Art, and Mathematics) in the process of making batik for the development of junior high school science teaching materials. This research method uses qualitative research with descriptive analysis of the Miles and Huberman model. The sampling technique in this study was purposive sampling which was collected through observation, in-depth interviews, documentation, and literature review. The results of this study indicate that the local wisdom of batik tulis Yogyakarta contains STEAM aspects in the manufacturing process and can be used as science learning material in junior high schools.